Journal Pengaruh Konseling Kelompok Dengan Teknik Cognitive Behavior Therapy Terhadap Peningkatan Kedisiplinan Siswa - Sabikun, Mad; Tawil, Tawil; Indiati, Indiati (Borobudur Counseling Review, 2021)
This study aims to determine the effect of group counseling with cognitive behavior therapy techniques to improving the level of indiscipline of students who have low self-catility in class VIII students of MTs Yajri Payaman, Secang District, Magelang Regency. This is evidenced by the difference in the mean score of the experimental group students' indiscipline scale. The results of the decrease in pretest and posttest scores were the highest score of 59 or (30.1%) and the lowest was 4 or (2.3%). The disciplinary average of the pretest and posttest students was 28.3 or (17.8%). The more the students' undisciplined scale score decreased, it proved that the effect of group counseling with cognitive behavior therapy techniques could reduce the level of indiscipline of the experimental class students. Keywords: Group Counseling, Cognitive Behavior Therapy, To Improve Student Disciplin